Banking deregulation and household consumption of durables - H. Evren Damar; Ian Lange; Caitlin McKennie; Mirko Moro (Halle Institute for Economic Research (IWH), 2020)
We exploit the spatial and temporal variation of the staggered introduction of interstate banking deregulation across the U.S. to study the relationship between credit constraints and consumption of durables. Using the American Housing Survey from 1981 to 1993, we link the timing of these reforms with evidence of a credit expansion and household responses on many margins. We find robust evidence that households are more likely to purchase new appliances and invest in home renovations and modifications after the deregulation. These durable goods allowed households to consume less electricity and spend less time in domestic activities after the reforms.
Additional information: A completely revised version of this paper has been published as Damar, H. Evren; Lange, Ian; McKennie, Caitlin; Moro, Mirko: Banking Deregulation and Consumption of Home Durables. IWH Discussion Papers 4/2022. Halle (Saale) 2021. http://hdl.handle.net/10419/249744; More recent version: http://hdl.handle.net/10419/249744
Keywords: D12; G2; Q41; 330; banking deregulation; credit constraints; energy consumption; durable goods